Exotic disordered phases in the quantum J1-J2 model on the honeycomb lattice - Zhang, Hao (2013)
We study the ground-state phase diagram of the frustrated quantum J 1-J2 Heisenberg antiferromagnet on the honeycomb lattice using a mean-field approach in terms of the Schwinger boson representation of the spin operators. We present results for the ground-state energy, local magnetization, energy gap, and spin-spin correlations. The system shows magnetic long-range order for 0≤J2/J1â‰0.2075 (Néel) and 0.398â‰J2/J1≤0.5 (spiral). In the intermediate region, we find two magnetically disordered phases: a gapped spin liquid phase, which shows short-range Néel correlations (0.2075â‰J2/J1â‰0. 3732), and a lattice nematic phase (0.3732â‰J2/J 1â‰0.398), which is magnetically disordered but breaks lattice rotational symmetry. The errors in the values of the phase boundaries, which are implicit in the number of significant figures quoted, correspond purely to the error in the extrapolation of our finite-size results to the thermodynamic limit.